Do Family Interventions Improve Outcomes in Early Psychosis? A Systematic Review and Meta-Analysis - Claxton, Melanie; Onwumere, Juliana; Fornells-Ambrojo, Miriam (Frontiers in Psychology, 2017)
Family interventions for psychosis (FIp) are effective in reducing service user relapse and carer distress in people with schizophrenia-spectrum conditions. Several treatment and best practice guidelines recommend FIp for all people with schizophrenia. However, outcome findings in relation to early psychosis groups have been inconsistent. The current paper reports a systematic review and meta-analyses of articles that evaluated FIp in early psychosis with a clearly defined comparison group. A combination of electronic database searches (using PsychINFO, Medline, and CENTRAL), citation searches and hand searches of key journals and reviews was conducted. Peer-reviewed articles published in English from database inception to June 2016 were included. Methodological quality was assessed using the Effective Public Health Practice Project Quality Assessment Tool (EPHPP). Seventeen papers from fourteen studies met inclusion criteria for review, the overall quality of which was moderate. Meta-analytic synthesis showed that FIp improved service user functioning and reduced the likelihood of relapse by the end of treatment. Psychotic symptoms were significantly reduced in the FIp group at follow up, but this was not evident at end of treatment. In terms of FIp target mechanisms, carers receiving FIp were more likely to shift from high to low expressed emotion and less likely to report patient focused criticism or engage in conflict communication than carers randomised to standard care. Carer burden and wellbeing were improved by the end of treatment but gains were not sustained at follow up. FIp had no impact on carer emotional over-involvement. The findings indicate that FIp is an effective intervention for early psychosis service users and their relatives. However, further research is required to establish which key therapeutic components of FIp are most effective for whom, in addition to understanding the mechanisms by which FIp might affect positive change.